Clinical Progress on Management of Pneumonia Due to COVID-19 With Chinese Traditional Patent Medicines - Wu, Ying; Zhong, Ping (Frontiers in Pharmacology, 2021)
Background: The outbreak of new coronavirus has tremendously threatened the public health system worldwide, including China. Chinese patent medicines (CPMs) have greatly contributed to the prevention and treatment of this viral infection, as well as the recovery of patients with COVID-19 infection. Therefore, numerous experts and guidelines recommend to take CPMs to treat pneumonia due to COVID-19. Aim of the Study: The present study reviewed CPMs recommended by the < Guidelines for diagnosis and management of COVID-19 (8th edition)> regarding evidence of their efficacy from clinical studies and the underlying mechanisms, which will lay the foundation for clinical use of these CPMs for COVID-19. Methods: The composition, efficacy, indications, history of use, and relevant clinical research on 14 recommended CPMs, including Huoxiangzhengqi capsules (pills, liquid, oral solution), Jinhuaqinggan granules, Lianhuaqingwen capsules (granules), Shufengjiedu capsules, Xiyanping injections, Xuebijing injections, Reduning injections, Tanreqing injections, Xingnaojing injections, Shenfu injections, Shengmai injections, Angongniuhuang pills, Suhexiang pills, were searched in both Chinese and English databases based on differences in stages of the disease and manifestations of such patients. Advantages of these CPMs over conventional treatments and their underlying mechanisms were explored by analyzing results from published articles and undergoing clinical trials. Results: Findings from clinical studies and Chinese experience in using these CPMs showed that CPMs, when used in combination with conventional treatments, were effective in managing COVID-19 with few side effects. Conclusion: CPMs have excellent efficacy in managing COVID-19 with a great potential for clinical use.